2011
DOI: 10.1007/s10584-011-0236-0
|View full text |Cite
|
Sign up to set email alerts
|

Interacting effects of vegetation, soils and management on the sensitivity of Australian savanna rangelands to climate change

Abstract: There is an increasing need to understand what makes vegetation at some locations more sensitive to climate change than others. For savanna rangelands, this requires building knowledge of how forage production in different land types will respond to climate change, and identifying how location-specific land type characteristics, climate and land management control the magnitude and direction of its responses to change. Here, a simulation analysis is used to explore how forage production in 14 land types of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 44 publications
(63 reference statements)
0
18
0
Order By: Relevance
“…The approach also provides a basis for a better understanding of future changes in landscape erodibility in response to the interacting effects of climate variability, climate change and grazing land management. Webb et al (2012) simulated forage production under various climate change scenarios for several land types in Queensland including the four in this study. They show that under hotter (+3°C) and wetter (+17% mean annual rainfall) climate, forage production could increase up to 60%, which should reduce the sensitivity of landscape to wind erosion and reduce accelerated wind erosion rates across if current grazing practices are maintained.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The approach also provides a basis for a better understanding of future changes in landscape erodibility in response to the interacting effects of climate variability, climate change and grazing land management. Webb et al (2012) simulated forage production under various climate change scenarios for several land types in Queensland including the four in this study. They show that under hotter (+3°C) and wetter (+17% mean annual rainfall) climate, forage production could increase up to 60%, which should reduce the sensitivity of landscape to wind erosion and reduce accelerated wind erosion rates across if current grazing practices are maintained.…”
Section: Discussionmentioning
confidence: 99%
“…They show that under hotter (+3°C) and wetter (+17% mean annual rainfall) climate, forage production could increase up to 60%, which should reduce the sensitivity of landscape to wind erosion and reduce accelerated wind erosion rates across if current grazing practices are maintained. Under a warmer (+2°C) and drier (À7% mean annual rainfall) climate or a hotter (+3°C) and drier (À46% mean annual rainfall) climate, Webb et al (2012) reported potential decreases in forage production as large as 90%. Combined with expected reductions in soil moisture under this scenario, we might expect land erodibility to increase across the study area.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations